Early Permian intrusions of the Alai range: Understanding tectonic settings of Hercynian post-collisional magmatism in the South Tien Shan, Kyrgyzstan - Konopelko, D.; Wilde, Simon; Seltmann, R.; Romer, R.; Biske, Y. (Elsevier BV, 2018)
© 2018 Elsevier B.V. We present geochemical and Sr–Nd–Pb–Hf isotope data as well as the results of single grain U–Pb zircon dating for ten granitoid and alkaline intrusions of the Alai segment of Kyrgyz South Tien Shan (STS). The intrusions comprise four geochemically contrasting series or suites, including (1) I-type and (2) shoshonitic granitoids, (3) peraluminous granitoids including S-type leucogranites and (4) alkaline rocks and carbonatites, closely associated in space. New geochronological data indicate that these diverse magmatic series of the Alai segment formed in a post-collisional setting. Five single grain U-Pb zircon ages in the range 287–281 Ma, in combination with published ages, define the main post-collisional magmatic pulse at 290–280 Ma, which is similar to ages of post-collisional intrusions elsewhere in the STS. An age of 287 ± 4 Ma, obtained for peraluminous graniodiorite of the Liayliak massif, emplaced in amphibolite-facies metamorphic rocks of the Zeravshan-Alai block, is indistinguishable from ca. 290 Ma age of peraluminous granitoids emplaced coevally with Barrovian-type metamorphism in the Garm block, located ca. 40 km south-west of the research area. The Sr-Nd-Pb-Hf isotopic compositions of the studied intrusions are consistent with the reworking of crustal material with 1.6–1.1 Ga average crustal residence times, indicating the formation of the Alai segment on a continental basement with Mesoproterozoic or older crust. The pattern of post-collisional magmatism in the Alai segment, characterized by emplacement of I-type and shoshoninitic granitoids in combination with coeval Barrovian-type metamorphism, is markedly different from the pattern of post-collisional magmatism in the adjacent Kokshaal segment of the STS with predominant A-type granitoids that formed on a former passive margin of the Tarim Craton. We suggest that during the middle-late Carboniferous the Alai segment probably comprised a microcontinent with Precambrian basement located between the Turkestan Ocean to the north and an inferred oceanic basin to the south, where the evidence of supra-subduction magmatism was largely destroyed by subsequent tectonic processes. In this scenario, after collision, the position of the Alai microcontinent between two major sutures enabled delamination of its lithospheric mantle, which resulted in production of diverse post-collisional magmatic series by interaction of ascending asthenospheric material with lithospheric mantle and various crustal protoliths.